PTU-005 Agreeing Endoscopy Trainer Attributes – a Delphi Study to develop a Trainer Evaluation Toolkit. (4th June 2013) - Macdougall, L; Corbett, S; Welfare, M; Wells, C; Barton, J R
Abstract : Introduction: Recent advances have been made to improve the skills of the UK's endoscopists but currently endoscopy trainers have no validated method by which to receive formative feedback regarding their training. Previous research has developed a list of attributes that describe the high quality trainer and could be used to deliver frequent feedback 1 . This study uses the Delphi technique to select and refine attributes to be included in an evaluation toolkit. The Delphi technique is a group consensus technique that involves asking a panel to take part in a series of rounds to clarify, refine and finally gain consensus on an issue. Methods: Four sub-groups (experts, trainers, nurse endoscopists and trainees) reviewed the list of attributes that describe good endoscopy trainers derived from previous work1. Participants were asked to suggest additions or modifications and rate the suitability of each attribute for two types of evaluation instrument: a single session (DOTS: directly observed teaching skills) or a rotation (LETS: long-term evaluation of teaching skills). After round one free text comments were analysed, additional items added and suggested modifications were made; attributes which scored less than 77% agreement were excluded; those that scored above 77% and had significantly different scores for the LETS and DOTS were allocated to the appropriate instrument. The remaining attributes were resubmitted to the panel in round 2 Results: 62 participants completed the process. Following free-text analysis it was apparent that the panel wanted tools that were as short as possible. The attributes were therefore re-grouped and similar attributes amalgamated. Remaining comments were reviewed and subsequent modifications made, 17 attributes were excluded in round 1; 8 were allocated to the DOTS and 9 to the LETS. In round 2 a further 12 attributes were allocated to the DOTS and 6 to the LETS and one new item added Conclusion: By conducting this study it has been possible to develop a usable evaluation toolkit by which trainers could gain formative feedback on their performance. The Delphi process has enabled us to reduce the number of attributes included in the toolkit and refine these attributes. It has also enabled us to gain and amalgamate the opinions of a large panel of experts. Due to suggestions made by the panel, the original wording of 13 of the attributes was refined. Five attributes have resulted from an amalgamation of attributes Disclosure of Interest: None Declared Reference: Wells, C., The characteristics of an excellent endoscopy trainer . Frontline Gastroenterology, 2010. 1 : p. 13–18.